Post‐transplant adjustment – The later years. (13th September 2014) - Fredericks, Emily M.; Zelikovsky, Nataliya; Aujoulat, Isabelle; Hames, Anna; Wray, Jo
Abstract As survival rates for pediatric solid organ transplantation have continued to improve, researchers and healthcare providers have increasingly focused on understanding and enhancing the HRQOL and psychosocial functioning of their patients. This manuscript reviews the psychosocial functioning of pediatric transplant recipients during the "later years, " defined as more than three yr post‐transplant, and focuses on the day‐to‐day impact of living with a transplant after the immediate period of adjustment and early years after surgery. Key topics reviewed include HRQOL, cognitive functioning, impact on the family, regimen adherence, and transition of responsibility for self‐management tasks. Overall, pediatric transplant recipients evidence impairment in HRQOL, neuropsychological outcomes, and family functioning as compared to non‐transplant recipients. However, the degree of impairment is influenced by a variety of factors including, disease severity, age, solid organ type, and study methodologies. Studies are limited by small samples, cross‐sectional design, and the lack of universal assessment battery to allow for comparisons across solid organ populations. Areas for future research are discussed.